2013
DOI: 10.4236/ijoc.2013.33030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TlOH Effect for Pd<sup>0</sup>-Mediated Cross-Coupling of Methyl Iodide and Excess Boronic Acid Ester toward Fabrication of [<sup>11</sup>C]CH<sub>3</sub>-Incorporated PET Tracer

Abstract: The use of thallium(I) hydroxide (TlOH) as a base is known to extremely accelerate the Suzuki-Miyaura cross-coupling reaction using organoboronic acid or organoboronic acid ester as a substrate. Here, we investigated the effects of TlOH by comparing with other conventional bases such as KOH, K 2 CO 3 , and CsF for Pd 0 -mediated rapid cross-coupling reactions between CH 3 I and organoborane reagents, such as phenyl-, (Z)-4-benzyloxy-2-butenyl-, and benzylboronic acid pinacol esters under the conditions CH 3 I/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Even the use of bulky phosphines at elevated temperatures gave much lower yield than our findings. Thus, it was concluded that the use of TlOH is not applicable to the cross-coupling reaction of CH 3 I and various types of organoborons substrates, reconfirming that the use of the milder and non-toxic bases, K 2 CO 3 or CsF, are most appropriate for rapid C-[ 11 C]methylation[84].…”
mentioning
confidence: 99%
“…Even the use of bulky phosphines at elevated temperatures gave much lower yield than our findings. Thus, it was concluded that the use of TlOH is not applicable to the cross-coupling reaction of CH 3 I and various types of organoborons substrates, reconfirming that the use of the milder and non-toxic bases, K 2 CO 3 or CsF, are most appropriate for rapid C-[ 11 C]methylation[84].…”
mentioning
confidence: 99%